7 - Work reorganisation and technological change: limits of trade union strategy and action at ArcelorMittal, Vanderbijlpark - Mondli Hlatshwayo,; Sakhela Buhlungu, (African Sociological Review, 2017)
The black South African trade unions were known globally for challenging apartheid in the workplace and low wages. In fact, they played a significant role in the broad liberation movement which ushered in democracy in 1994. However, little is known about the unions’ ability to respond to production issues such as technological changes at the ‘point of production’. Using a case study of the Vanderbijlpark Plant currently owned by the global steel corporation ArcelorMittal International, this article shows that the National Union of Metal Workers of South Africa (NUMSA) - the biggest trade union in South Africa - adopted a bargaining strategy which consistently ignored production issues at the plant while focusing on wages and working conditions. This article suggests that this unidimensional strategy meant that building the union’s capacity was neglected, reducing its ability to respond proactively to technological innovation and work reorganisation. While it does not present union capacity as a panacea, the article presents international examples that indicate that unions with more developed research and education capabilities were able to save some jobs by engaging union members and proposing alternatives.